Ocorrência de biguatinga, Anhinga anhinga L., 1766 (Pelecaniformes: Anhingidae), no município de Florestal, Minas Gerais, Brasil - Resende Monteiro, Alberto; de Mattos, Geraldo Theodoro (Revista Ceres, 2025)
One young female Anhinga anhinga, Linnaeus 1766-Pelecaniformes: Anhingidae, was found in Florestal (MG), evidence that this bird exist in restricted area in Minas Gerais State. This record is very important because this bird is very scarce in Minas Gerais and others states of Brazil.